Health‐related quality of life in infants and children with interstitial lung disease. Issue 6 (13th March 2019) - Lauby, Clara; Boelle, Pierre‐Yves; Abou Taam, Rola; Bessaci, Katia; Brouard, Jacques; Dalphin, Marie‐Laure; Delacourt, Christophe; Delestrain, Céline; Deschildre, Antoine; Dubus, Jean‐Christophe; Fayon, Michaël; Giovannini‐Chami, Lisa; et al.
Abstract: Introduction: Interstitial lung disease in children (chILD) is a highly heterogeneous group of rare and severe respiratory disorders. The disease by itself, the burden of the treatments (oxygen therapy, corticosteroid pulses, nutritional support) and recurrent hospitalizations may impair the quality of life (QoL) of these children. The aim of the study was to compare the health‐related QoL (HR‐QoL) in chILD compared to a healthy population and to find out the predictive factors of an altered QoL. Methods: Patients aged 1 month to 18 years with ILD of known or unknown etiology were prospectively included. Parents and children over 8 years old were asked to fill the PedsQL 4.0 Generic Core Scale ranging from 0 to 100 points. Results: A total of 78 children were recruited in 13 French pediatric centers. Total scores were 11.94 points ( P  = 0.0003) less for child self‐report and 14.08 points ( P  < 0.0001) less for parent proxy‐report with respect to the healthy population. The clinical factors associated with a lower total score were: extrapulmonary expression of the disease, higher Fan severity score, long‐term oxygen therapy, nutritional support, and a number of oral treatments. Conclusion: Using a validated quality of life (QoL) scale, we showed that health‐related‐QoL is significantly impaired in chILD compared with a healthy population. Factors altering QoL score are easy to recognize and could help identify children at a heightened risk of low QoL.